2003
DOI: 10.1590/s0103-90162003000200005
|View full text |Cite
|
Sign up to set email alerts
|

Stomatal responses of Eucalyptus species to elevated CO2 concentration and drought stress

Abstract: Five species of Eucalyptus (E. grandis, E. urophylla, E. camaldulensis, E. torelliana, and E. phaeotrica), among the ten species most commonly used in large scale plantations, were selected for studies on the effects of elevated CO 2 concentration [CO 2 ] and drought stress on stomatal responses of 2.5-month old seedlings. The first three species belong to the subgenus Smphyomyrtus, whereas the fourth species belongs to the subgenus Corymbia and E. phaeotrica is from the subgenus Monocalyptus. Seedlings were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
12
0
6

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 40 publications
6
12
0
6
Order By: Relevance
“…This suggests that photoinhibition, often considered one of the effects of water stress (BJÖRKMAN;DEMMING, 1987;MOSETI;DINTWE, 2011), did not occur in this experiment, as observed by Rolando and Litttle (2008) in seedlings of E. grandis, and by Correia et al (2014) in E. globules subjected to water stress. Like those authors, it is possible to conclude that the Fv/Fm ratio does not reflect the water status of the plants, differing from results found by Lima, Rhizopoulou and Jarvis (2003). When a plant has its photosynthetic apparatus intact, the Fv/Fm ratio is close to 0.82, while a fall in this ratio reflects the presence of photoinhibition damage to the reaction centres of photosystem II (BJORKMAN;DEMMING, 1987).…”
Section: Figure 1 -Photosynthetic Rate (A and D) Stomatal Conductancmentioning
confidence: 85%
See 1 more Smart Citation
“…This suggests that photoinhibition, often considered one of the effects of water stress (BJÖRKMAN;DEMMING, 1987;MOSETI;DINTWE, 2011), did not occur in this experiment, as observed by Rolando and Litttle (2008) in seedlings of E. grandis, and by Correia et al (2014) in E. globules subjected to water stress. Like those authors, it is possible to conclude that the Fv/Fm ratio does not reflect the water status of the plants, differing from results found by Lima, Rhizopoulou and Jarvis (2003). When a plant has its photosynthetic apparatus intact, the Fv/Fm ratio is close to 0.82, while a fall in this ratio reflects the presence of photoinhibition damage to the reaction centres of photosystem II (BJORKMAN;DEMMING, 1987).…”
Section: Figure 1 -Photosynthetic Rate (A and D) Stomatal Conductancmentioning
confidence: 85%
“…The physiological and biochemical changes most commonly observed as the responses of plants to drought include closure of the stomata (with a consequent reduction in stomatal conductance, the rate of photosynthesis and transpiration), reduced water potential and water content of the leaves, an increase in the synthesis of osmoprotectors (proline and sugars), protein degradation (FANAEI et al, 2009) and a reduction in the photochemical efficiency of photosystem II, given by the ratio between the variable and maximal fluorescence -Fv/ Fm (BJÖRKMAN; DEMMING, 1987;LIMA, JARVIS, RHIZOPOULOU, 2003;MOSETI;DINTWE, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…nitens, andWhitehead &Beadle (2004), Mendes, de Paula, Scarpinatti &de Paula (2013), andEl-Sharkawy et al (1985), in E. deglupta and E. citriodora. Lima et al (2003), found in several Eucalyptus species (E. grandis, E. urophilla, E. camaldulensis, E. torelliana and E. phaeotrica) photosynthesis rates between 25-30 μmol CO 2 m -2 s -1 with atmospheric CO 2 concentrations of 700 ppm (± 30) in the dry season, whereas rates of photosynthesis were 10-15 μmol CO 2 m -2 s -1 at normal concentrations of 350 ppm (± 30).…”
Section: Discussionmentioning
confidence: 94%
“…Research conducted by Close & Davidson (2003), in E. nitens, Sena &Kozlowski (1980), in E. camaldulensis andE. globulus, andLima, Jarvis, &Rhizopoulou (2003), in E. grandis, E. urophilla, E. camaldulensis, E. torelliana andE. phaeotrica, show the formation of adventitious roots and aerenchyma in response to periods of prolonged waterlogging, in addition to reducing the photosynthesis rate and significantly decreasing plant height and root and leaf production in trees of E. robusta (Clemens, Kirk, & Mills, 1978).…”
Section: Introductionmentioning
confidence: 99%
“…The positive influence of clay content on productivity is mainly due to increase of available water content in the soil (Figure 4). Lopes (1977) also found higher Zakia, 1998;Lima et al, 2003). Because of this, the soil's water regime is one of the most important factors that determine productive capacity (Melo et al, 1995;Leite, 1996).…”
Section: Resultsmentioning
confidence: 99%